Shave Excision Of Marginal Lower Eyelid Nevus: Poster Presentation - Case Report - Resident - Rika Karim Chan; Prof. Dr. dr. Rodiah Rahmawaty Lubis, M.Ked(Oph), SpM(K) (Majalah Oftalmologi Indonesia, 2023)
Introduction : INTRODUCTION: Nevus is a common benign melanocytic lesion and may appear in palpebral region. It may appear congenitally or acquired. Such lesions contain melanocyte derived from neural crest. Palpebral nevus is a group of heterogenous lesion with varying clinical and histological presentation depending on age and nevus stage. PURPOSE: To report shave excision procedure of the left inferior palpebral nevus located in the palpebral margin using local anesthesia. Case Illustration : CASE REPORT: A 43-years old woman came to the hospital with a solitary mass in the lower right eyelid. The mass was experienced since 2 year ago and slowly increasing in size and most notably 3 months prior. The mass was round, tender, painless, black-greyish colored, with a smooth surface, mobile, and measured 0,5 cm x 0,5 cm in size. The lesion was located in the middle portion of right lower palpebral margin without extension to the tarsal or bulbar conjunctiva. No bleeding or discharge was found. No history of trauma, use of medication, family history, previous ocular and systemic disease was found. Histopathological examination concluded the lesion was nevus pigmentosus. The nevus was excised entirely using shave excision technique with local anesthesia. Follow-up examination revealed an excellent result with no complications. Discussion : Conclusion : CONCLUSION: Palpebral nevus pigmentosus are common benign tumor with wide range of clinical and histological manifestation. Not all palpebral nevus required surgical intervention. The most effective treatment is complete excision of the nevus and recurrence rate is generally low.